FACTORS INFLUENCING MANAGEMENT STUDENTS’ UNDERSTANDING THE ENGLISH TERMINOLOGY IN MANAGEMENT REPORTS - Marpurdianto, Kharis; Hardono (Srawung: Journal of Social Sciences and Humanities, 2023)
The communication is very important in business. The good communication between producers, distributors, and consumers will increase the effectiveness of entrepreneurial activities. This research aims to examine the factors which affected management students’ understanding of English terminology in Management reports. The qualitative descriptive analysis is used in this research since it aims to describe a phenomenon and its characteristics. The sample population in this research consists of 151 students enrolled in first semester of 2022-2023 academic year at Management Department of Economics and Business faculty at Universitas Wijaya Kusuma Surabaya. Based on the research result, the management students’ ability to comprehend the English vocabulary used in business reports depends on several things, including students’ limited command of English, their desire to learn English to support their comprehension of foreign languages, and their limited access to sources of information about the English terms used in business reports. The most effective way to understanding English terminology in management report is to translate the English terminology into the local tongue using cultural factors, context, and translation techniques to produce word harmonization in local tongue.